Islamic Acculturation In The Ancestors’ Legacy Of Nanga Suhaid Village, West Kalimantan - Bibi Suprianto (Jurnal Dialog, 2020)
This paper attemps to describe how Islamic acculturation was formed in the tradition of Nanga Suhaid Village, West Kalimantan. This paper shed light on community activities in relation to religious interactions, especially in the inner part of the West Kalimantan region, namely Suhaid Sub-district Nanga Suhaid village, Kapuas Hulu district. This study utilized observation, interview, and documentation for data collection through the lens of an anthropological perspective. The results of the study showed: 1) practice of the tradition in the Suhaid village that has long been carried out is a means to maintain the existing traditions. 2) the expression of Islamic Da’wah values could be seen from "buang-buang", plain flour, circumcision, customary law, fruit and da’wah values. 3) The tradition of maintained tolerance within the community to create peace and harmony in the community. Makalah ini berupaya mendeskripsikan akulturasi Islam pada tradisi nenek moyang di desa Nanga Suhaid, Kalimantan Barat. Makalah ini berfokus pada kegiatan-kegiatan masyarakat dan interaksi agama yang saling mendukung khususnya daerah pendalaman kepulauan Kalimantan Barat kecematan Suhaid, desa Nanga Suhaid kabupaten Kapuas Hulu. Penelitian ini menggunakan metode wawancara, observasi dan dokumentasi serta pendekatan antropologis pada masyarakat. Hasil penelitian 1) penerapan tentang tradisi-tradisi desa Suhaid yang telah dilaksanakan sebagai gambaran budaya setempat untuk mempertahankan tradisi yang telah ada. 2) mengambil nilai-nilai dakwah Islam yang ada pada tradisi seperti buang-buang, tepung tawar, sunatan/ khitanan, hukum adat, beruah dan nilai-nilai dakwah. 3) Akulturasi Islam pada tradisi nenek moyang yang selalu menjaga toleransi sesama agar terciptanya kedamaian dan ketentraman pada masyarakat.